2009
DOI: 10.1007/s11615-009-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Eine Disziplin auf der Suche nach Wissenschaftlichkeit: Entwicklung und Stand der Methoden in der deutschen Politikwissenschaft

Abstract: Zusammenfassung: Der Aufsatz befasst sich mit einer Bestandsaufnahme der Methodenanwendung in der deutschen Politikwissenschaft. Auf der Grundlage einer Auswertung der Aufsätze in vier deutschen politikwissenschaftlichen Fachzeitschriften wird aufgezeigt, dass nur eine Minderheit explizit theoriegeleitet-empirische Forschung betreibt. Ein Großteil der Publikationen hat eher den Charakter der sachkundigen Erörterung eines Themas. Dieser Befund wird ergänzt durch eine Positionierung Deutschlands im international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
(37 reference statements)
1
5
0
2
Order By: Relevance
“…This might in part explain the still comparatively small share of ambitiously quantitative studies found here. Kittel (2009) draws a similar conclusion. On the other hand, many of the international journals included in Plümper's study are not typical outlets for highly quantitative research.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This might in part explain the still comparatively small share of ambitiously quantitative studies found here. Kittel (2009) draws a similar conclusion. On the other hand, many of the international journals included in Plümper's study are not typical outlets for highly quantitative research.…”
Section: Discussionsupporting
confidence: 60%
“…This growing rate of collaborative research, in itself, is the result of increasing pressure for younger academics to spend time conducting research abroad and receiving better training in the most recent methods used in political research. This, in turn, makes them more attractive in the German academic job market (Kittel, 2009). Plümper and Schimmelfennig (2007) also found that publications in peer-reviewed international journals are among the most important factors in explaining job market success of new professors of political science in Germany, ahead of even peer-reviewed publications in German-language journals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A map of methods is also, to a large extent, a map of a discipline. As shown in bibliometrics studies of political science since the 1960s in Germany (Kittel, 2009;Pehl, 2012), methodological tracks connect with disciplinary subfields. Systematic reviews from journals and curricula in the USA, France, the UK and Germany (Bennett, Barth and Rutherford, 2003;Boncourt, 2007;Kittel, 2009) also illustrate how methods develop in connection with the discipline's growth and coherence.…”
Section: Why We Need To Map Methodsmentioning
confidence: 99%
“…Die vorliegenden Lernmaterialien lassen sich hervorragend in der universitären Lehre einsetzen und ermöglichen es, traditionelle Lehrformate zu erweitern. E-Lernen ist in diesem Bereich weit fortgeschritten, die E-Lernmaterialien sind konsolidiert und werden konti- (Dreiack et al 2016;Engel 2002;Kittel 2009).…”
Section: Drei Entwicklungenunclassified